Delineation of two clinically and molecularly distinct subgroups of posterior fossa ependymoma - Witt, Hendrik; Mack, Stephen C.; Ryzhova, Marina; Bender, Sebastian; Sill, Martin; Isserlin, Ruth; Benner, Axel; Hielscher, Thomas; Milde, Till; Remke, Marc; Jones, David T. W.; Northcott, Paul A.; et al. (Cancer cell, 2011)
Despite the histological similarity of ependymomas from throughout the neuroaxis, the disease likely comprises multiple independent entities, each with a distinct molecular pathogenesis. Transcriptional profiling of two large independent cohorts of ependymoma reveals the existence of two demographically, transcriptionally, genetically, and clinically distinct groups of posterior fossa (PF) ependymomas. Group A patients are younger, have laterally located tumors with a balanced genome, and are much more likely to exhibit recurrence, metastasis at recurrence, and death compared with Group B patients. Identification and optimization of immunohistochemical (IHC) markers for PF ependymoma subgroups allowed validation of our findings on a third independent cohort, using a human ependymoma tissue microarray, and provides a tool for prospective prognostication and stratification of PF ependymoma patients.